Perancangan Sistem Terintegrasi Produksi Ragum Custom di SSML - Reza Aditya Fauzi; Rijki Nurlaeli; Muhamad Ridwan; Muhammad Harsya Alfarisi; Lisye Fitria (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Small Scale Manufacturing Laboratory (SSML) has the capability to manufacture custom vises based on customer requirements and specifications. However, the ordering and production management processes are still performed manually, resulting in limited coordination and production monitoring. This study aimed to design an integrated Engineer-to-Order (ETO)-based production system for custom vises with ordering and production monitoring features. The research employed a Research and Development (R&D) approach consisting of needs identification, literature review, system design, production process simulation using FlexSim, and the development of Standard Operating Procedures (SOPs) and Occupational Safety and Health (OSH) procedures. The results indicate that the proposed system integrates order management, product specification management, production progress monitoring, and production time estimation into a structured platform. Customer and administrator dashboards improve information management, while the production simulation visualizes workflow prior to operational implementation. The proposed system has the potential to enhance the effectiveness of custom vise production management and improve service quality for both internal and external customers.